2020
DOI: 10.1088/1757-899x/935/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Methanol soluble extractives of Pinus merkusii bark and its antioxidant activity

Abstract: The major function of bark in trees is to protect the living tissues. This is due to the chemical extractives in the bark such as polyphenols and terpenoids. In Indonesia, the bark of Pinus merkusii is of high economic value due to its use in the production of wood and oleoresins. Also, the presence of polyphenols in its bark has the potential of being used as antioxidant agents. Based on this, the aim of this study was to investigate antioxidant activity from the methanol extract of P. merkusii bark. This met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Various studies have reported that P. merkusii contains a relatively high amount of total phenolic content and total flavonoid content. According to Masendra et al [ 10 ], total phenolic content and total flavonoid content P. merkusii bark are in the range of 421.4–486.5 mg GAE/g and 55.2–367.4 mg CE/g, respectively. In another study, Aloui et al [ 11 ] reported that pine resin shows a promising bioactivity with an antioxidant activity (IC 50 ) in the range of 15 ± 0.59 mg/mL to 17 ± 0.11 mg/mL and antibacterial capacity with an average inhibition zone diameter of 1.46–2.13 cm.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported that P. merkusii contains a relatively high amount of total phenolic content and total flavonoid content. According to Masendra et al [ 10 ], total phenolic content and total flavonoid content P. merkusii bark are in the range of 421.4–486.5 mg GAE/g and 55.2–367.4 mg CE/g, respectively. In another study, Aloui et al [ 11 ] reported that pine resin shows a promising bioactivity with an antioxidant activity (IC 50 ) in the range of 15 ± 0.59 mg/mL to 17 ± 0.11 mg/mL and antibacterial capacity with an average inhibition zone diameter of 1.46–2.13 cm.…”
Section: Introductionmentioning
confidence: 99%